The grammatical acquisition of wh-questions in early English multi-word speech - Rowland, Caroline F. (2000)
Recent studies of wh-question acquisition have tended to come from the nativist side of the language acquisition debate with little input from a constructivist perspective. The present work was designed to redress the balance, first by presenting a detailed description of young children's wh-question acquisition data, second, by providing detailed critiques of two nativist theories of wh- question acquisition, and third, by presenting a preliminary account of young children's wh-question development from a constructivist perspective. Analyses of the data from twelve 2 to 3 year old children collected over a year and of data from an older child (Adam from the Brown corpus, 1973) are described and three conclusions are drawn. First it is argued that the data suggest that children's knowledge of how to form wh-questions builds up gradually as they learn how to combine lexical items such as wh-words and auxiliaries in specific ways. Second, it is concluded that two nativist theories of grammatical development (Radford, 1990, 1992, 1995, 1996, Valian, Lasser & Mandelbaum, 1992) fail to account successfully for the wh-question data produced by the children. Third, it is asserted that the lexically-specific nature of children's early wh-questions is compatible with a lexical constructivist view of development, which proposes that the language learning mechanism learns by picking up high frequency lexical patterns from the input. The implications of these conclusions for theories of language development and future research are discussed.